Distribution of microglial phenotypes as a function of age and Alzheimer's disease neuropathology in the brains of people with Down syndrome. Issue 1 (14th October 2020) - Martini, Alessandra C.; Helman, Alex M.; McCarty, Katie L.; Lott, Ira T.; Doran, Eric; Schmitt, Frederick A.; Head, Elizabeth
Abstract: Introduction: Microglial cells play an important role in the development of Alzheimer's disease (AD). People with Down syndrome (DS) inevitably develop AD neuropathology (DSAD) by 40 years of age. We characterized the distribution of different microglial phenotypes in the brains of people with DS and DSAD. Methods: Autopsy tissue from the posterior cingulate cortex (PCC) from people with DS, DSAD, and neurotypical controls was immunostained with the microglial marker Iba1 to assess five microglia morphological types. Results: Individuals with DS have more hypertrophic microglial cells in their white matter. In the gray matter, individuals with DSAD had significantly fewer ramified microglia and more dystrophic microglia than controls and the younger individuals with DS. The DSAD group also exhibited more rod‐shaped and amoeboid cells than the AD group. Discussion: Individuals with DS and DSAD show a microglial phenotype that distinguishes them from non‐DS controls.